Forbidden music : the Jewish composers banned by the Nazis - Haas, Michael, 1954- (Yale University Press, 2013)
When National Socialism arrived in Germany in 1933, Jews dominated music more than virtually any other sector, making it the most important cultural front in the Nazi fight for German identity. This groundbreaking book looks at the Jewish composers and musicians banned by the Third Reich and the consequences for music throughout the rest of the 20th century.